A One‐Step Approach to the Synthesis of High Aspect Ratio Titania Nanoflakes - Scott Brown; Hassan El‐Shall; Yang‐Yao Lee (Global Challenges, 2017)
Abstract High aspect ratio TiO2 nanoflakes are synthesized by a one‐step modified surface hydrolysis method. Surface morphology and physical dimensions are characterized using scanning electron microscopy, laser diffraction analysis, and transmission electron microscopy. Microsized flakes having a thickness ≈40 nm are successfully synthesized by spreading an oil phase consisting of titanium tetraisopropoxide and a low surface tension hydrocarbon on the surface of water. Pure anatase phase crystalline titania nanoflakes are obtained by calcining at 400 °C without changing the shape and thickness of flakes. Relatively higher specific surface area (2–6 times) and less crystal defects enhance photocatalytic activities of nanoflakes due to more surface reaction sites and the suppression of fast recombination. By performing dye degradation under ultraviolet illumination, titania nanoflakes exhibit the higher photocatalytic efficiency over the commercial photocatalyst, Degussa P25. As far as it is known, this method is the most efficient and cost effective process for making low‐dimensional nanomaterials in a continuous manner. These titania flakes can be easily separated from the treated water by simply sedimentation or filtration and therefore is very suitable for water purification application.